2007
DOI: 10.1063/1.2434962
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nonlinear acoustic cavitation dynamics in liquid CO2

Abstract: The authors present a model to study ultrasound-induced cavitation dynamics in liquid carbon dioxide ͑CO 2 ͒, which includes descriptions for momentum, mass, and energy transport. To assist in the interpretation of these results, numerical simulations are presented for an argon cavity in water. For aqueous systems, inertia effects and force accumulation lead to a nonlinear radial motion, resulting in an almost adiabatic compression of the cavity interior. The simulations for liquid CO 2 suggest that transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…13 In accordance with this work, high-speed images acquired during the sonication of a similar mixture confirm that the cavities display hardly any radial motion. Although the experimental conditions have been varied extensively, nonlinearly oscillating cavities cannot be resolved from these images, thereby suggesting that acoustic cavitation does not occur in pressurized CO 2 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…13 In accordance with this work, high-speed images acquired during the sonication of a similar mixture confirm that the cavities display hardly any radial motion. Although the experimental conditions have been varied extensively, nonlinearly oscillating cavities cannot be resolved from these images, thereby suggesting that acoustic cavitation does not occur in pressurized CO 2 .…”
Section: Resultssupporting
confidence: 68%
“…Recent numerical modeling work has demonstrated that nonlinear cavity dynamics in high-pressure CO 2 appears improbable. 13 The present work elaborates on this numerical study and investigates the governing processes upon sonication of pressurized CO 2 by means of high-speed visualization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the present paper, a quantitative analysis of non-spherical bubbles is also given for determining bubble instability in order to check the validity of the assumption of spherical bubbles employed in our model. Other applications of our approach include the development of high-frequency acoustic camera for high resolution imaging in turbid water [40,41] and green solvent using high-pressure liquid carbon dioxide [42][43][44] (noticing that large kR 0 in this case due to the limited value of sound speed).…”
Section: Introductionmentioning
confidence: 99%
“…40,42 Although it is unclear that a nonzero temperature difference T w À h w need be considered, 41 this modeling component is included for generality and consistency with prior work. 43,44 Although it is difficult to extrapolate the results from kinetic gas simulations to the conditions present in a collapsing bubble, values of f calculated by Sharipov and Kalempa 40 suggest that likely values range from about 2 to 2.5. We select a value f ¼ 2 here as a round number-results suggest that the model is not sensitive to this parameter.…”
Section: Heat Transportmentioning
confidence: 99%
“…Many of the same or similar formulations have been used in previous bubble models. 35,43,47 In the table, note that the properties are divided into three groups: in the top group, properties are initialized and not updated during integration; in the middle group, properties are updated after each integration time step; in the bottom group, properties are updated during each time step as an inherent part of the integration. To evaluate any fluid property under conditions beyond the range specified for the referenced correlation, the closest conditions within the specified range were used.…”
Section: Fluid Propertiesmentioning
confidence: 99%